2020
DOI: 10.3126/nmcj.v22i3.32640
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease among Pregnant Women at a Tertiary Care Hospital in Kathmandu

Abstract: Pregnancy is characterized by many significant changes in a woman’s body which helps develop the fetus optimally. During pregnancy, there is marked maternal endocrine upregulation, hormonal profile modifications and interactions leading to dry eyes. Pregnancy causes most parts of a woman’s body to change, and the eyes are no exception. Dry eye disease is a common pregnancy problem that usually begins towards the end of the first trimester. Since, there is a dearth of literature on dry eye disease during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Consistent with the results of previous hospital-based studies in developing countries [15][16][17][18] , myopia had the highest prevalence. Contrarily, hyperopia was the most occurring refractive error recorded among rural Zimbabweans 7 .…”
Section: Resultssupporting
confidence: 91%
“…Consistent with the results of previous hospital-based studies in developing countries [15][16][17][18] , myopia had the highest prevalence. Contrarily, hyperopia was the most occurring refractive error recorded among rural Zimbabweans 7 .…”
Section: Resultssupporting
confidence: 91%
“…However, according to the SPEED score criteria, only 1.2% of pregnant women had subjective symptoms of dry eye (moderate dry eye score). A recent study, by Rizyal et al reported that dry eye prevalence among pregnant women varies between 27.4% and 89.3% depending on the clinical criteria like tear breakup time and Schirmer's test used for dry eye diagnosis [ 30 ]. In fact, in a hospital-based cross-sectional study of pregnant women, 40.8% of dry eye disease was diagnosed with clinical dry eye tests and dry eye questionnaire [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A szemszárazság jellemzően a terhesség első tri meszterének végén jelentkezik, előfordulása a gestatiós hetek előrehaladtával megnő, és a szülést követően még hónapokig fennáll. A szárazszemtünetek terhesség alatt gyakoriak, különböző tanulmányok a gravidák 30-80% ában igazolták, többségük azonban panaszmentes volt [5].…”
Section: Szemszárazság éS Kontaktlencse-intoleranciaunclassified
“…Ezen tényezők a kon taktlencseviselést megnehezítik és veszélyessé tehetik, mivel szaruhártyagyulladásra, súlyosabb esetben pedig szaruhártyafekély kialakulására is hajlamosíthatnak. A terhesség során jelentkező panaszok esetén a kontaktlen cseviselés átmeneti felfüggesztése javasolt [1,5].…”
Section: Szemszárazság éS Kontaktlencse-intoleranciaunclassified